Culture and corruption - Barr, A; Serra, D (University of Oxford, 2006)
Working with a sample of individuals from 43 countries, including some of the most and least corrupt in the world, we run an experiment in which: 'private citizens' have to decide whether and how much to offer 'public servants' in exchange for corrupt services; 'public servants' have to decide whether and how much to accept; and offered and accepted bribes do harm to other members of society. We can predict who, among the younger members of our sample, will offer bribes with reference to the level of corruption prevailing in their home countries. And, by comparing behaviour across treatments, we can identify the effect on behaviour of an internalized social norm or preference for not engaging in bribery because it is harmful to society. We conclude that corruption is, in part, a cultural phenomenon.